2010
DOI: 10.1124/dmd.110.032367
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A4 Catalytic Activity Is Induced in Confluent Huh7 Hepatoma Cells

Abstract: ABSTRACT:Drug-induced hepatotoxicity is an important cause for disapproval, limitations of use, or withdrawal of drugs, and there is a high need for reproducible in vitro systems that can predict such toxicity. In this study, we show that confluent growth of the human hepatoma cell line Huh7 up to 5 weeks results in increased gene expression of several cytochromes P450 (P450s), UDP-glucuronosyltransferases, transporters, transcription factors, and several liver-specific genes, as measured by low-density array.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 35 publications
3
47
0
Order By: Relevance
“…Previously, we have shown that Huh7 cells grown confluent up to 4 weeks achieve a more differentiated phenotype more similar to primary hepatocytes (Sivertsson et al, 2010). To investigate the change in gene expression during this phenotypical switch, a global gene expression analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we have shown that Huh7 cells grown confluent up to 4 weeks achieve a more differentiated phenotype more similar to primary hepatocytes (Sivertsson et al, 2010). To investigate the change in gene expression during this phenotypical switch, a global gene expression analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Four-weeks confluent and subconfluent control cells, grown on glass cover slips, were fixed and stained as previously described (Sivertsson et al, 2010). The slides were incubated with goat anti-PXR (sc-9690; Santa Cruz Biotechnology) or rabbit anti-CDK2 (sc-163; Santa Cruz Biotechnology) antibodies, followed by anti-goat Cy3 (Jackson Immunoresearch, West Grove, PA) or anti-rabbit Alexa Fluor 488 (Invitrogen) conjugated antibodies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Western Blot Analysis-Subcellular fractions isolated from rat liver and cell lysates from adipocytes and preadipocytes were subjected to Western blot analysis as described previously (22).…”
Section: Purification Of Outer Mitochondrial Membranes From Ratmentioning
confidence: 99%